East war from close: diary of Petras Plevokas - Vareikis , Vygantas; Vareikis , Vygantas (Genocidas ir rezistencija, 2007)
Petras Plevokas, a senior chief of the Lithuanian Police Protection Battalion, died a soldier’s death at the front fighting the Bolsheviks. The diary, damaged by humidity, was found by Russian soldiers on 28 February 1942, as it is written at the top of the document, ‘on the killed officer in the village of Semionov, Drogobuzhenov district’. Later on, the NKVD interrogators, reading this diary and apparently looking for ‘traitors to the fatherland’, underlined the facts that particularly interested them, as well as all the names of soldiers and officers. In the late 1960s, Švyturys, which was then a KGB mouthpiece, published several fragments of Plevokas’ diary, illustrating the usual ideological claims that Lithuanian ‘bourgeois nationalists’ were serving the German fascists.
Keywords: German occupation; Second World War; diary; documents